ANALISIS FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP RETURN SAHAM LQ 45 DI BURSA EFEK INDONESIA TERKAIT DENGAN KRISIS GLOBAL 2008 SEBAGAI VARIABEL MODERATING (Research Institution and Community Service Wijaya Kusuma Surabaya University, 2013)
The purpose of this study are to identify 2008 global crisis in moderating influence of liquidity ratio, influence of solvency, influence of profitability ratio, influence of activity ratio to LQ45 stock return during 2006-2010 in Indonesia Stock Exchange. This study used secondary datac from company annual report is included in LQ45 during 2006-2010. This study used secondary data. Sources of data derived from company annual report is included in LQ45 category shares during 2006-2010. Variables used in this study are Stock Return, Current Ratio (CR), Debt to Equity Ratio (DER), Return on Assets (ROA), and Total Asset Turnover (TATO), and the Global Crisis (KG). Stock return is dependent variable and Global Crisis as a moderating variable. This study used descriptive analysis and multiple linear regression analysis.Based on used of analysis model is known that there are no problems of classical assumptions include linearity, multicollinearity, autocorrelation, heteroscedasticity, and normality. This study shows that simultaneous variable liquidity, solvency, profitability, and activity affect LQ45 stock return. Partially, the global crisis did not affect the relation between liquidity ratios, solvency ratios, profitability ratios and activity ratios of LQ45 stock return.